2020
DOI: 10.18632/aging.102703
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates the advanced maternal age-associated meiotic defects in oocytes through the SIRT2-dependent H4K16 deacetylation pathway

Abstract: It has been widely reported that advanced maternal age impairs oocyte quality. To date, various molecules have been discovered to be involved in this process. However, prevention of fertility issues associated with maternal age is still a challenge. In the present study, we find that both in vitro supplement and in vivo administration of melatonin are capable of alleviating the meiotic phenotypes of aged oocytes, specifically the spindle/chromosome disorganization and aneuploidy generation. Furthermore, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…One of the most effective means is maintain the balance of intracellular redox state in aged oocytes through exogenous supplementation of antioxidant compounds. The typical antioxidants such as melatonin 10 12 , resveratrol 13 – 15 , N‐acetyl‐L‐cysteine 16 , Coenzyme Q10 17 , etc., have been proved to improve the aged oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective means is maintain the balance of intracellular redox state in aged oocytes through exogenous supplementation of antioxidant compounds. The typical antioxidants such as melatonin 10 12 , resveratrol 13 – 15 , N‐acetyl‐L‐cysteine 16 , Coenzyme Q10 17 , etc., have been proved to improve the aged oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of maternal age on antioxidants, we found that only melatonin levels were significantly affected during the first month of breastfeeding, also confirmed by the linear model. Maternal age is one of the main factors limiting antioxidant production in humans, as established by previous studies, and extensively demonstrated for melatonin [49,50]. Melatonin levels in plasma are known to decline with age [51] and plasma concentrations match those found in BM [38].…”
Section: Discussionmentioning
confidence: 63%
“…SIRT2 is a key effector of oocyte meiosis, and SIRT2-controlled histone H4K16 deacetylation is essential for oocyte meiosis. Li et al revealed that melatonin could improve oocyte quality in aged mice through the SIRT2-dependent H4K16 deacetylation pathway [ 28 ]. Also, melatonin could counteract mitochondrial oxidative damage via SIRT3/FOXO3a pathway.…”
Section: Melatonin Delays Ovarian Agingmentioning
confidence: 99%